Pendampingan Guru SMKS Prima Bakti Dalam Membuat Modul Praktek dan Trainer Kit Elektronika Dasar, Tangerang - Wildan, Muh; Purwaningtyas, Dian Anggraini; Eriyandi; Wahyudi, Johan; Roza, Febria; Ermawati, Leni Tri; Arafi , Thoriq (Politeknik Penerbangan Indonesia Curug, 2025)
Vocational school students are vocational schools that are at the forefront of the industrial world. This Community Service (PKM) activity was carried out based on concerns about the condition of several vocational schools with practical facilities that were still below standard. The responsibility of universities is not only to produce students but also to improve the surrounding area so that the benefits are also felt in society. The PKM scheme that will be implemented is an Assisted School-based Scheme (PKM-SB). PKM's partner is Prima Bakti Vocational School with a